Respostas

2014-08-04T00:04:01-03:00
Xy=1
x-2y=1 --> x=1+2y

(1+2y)y=1
y+2y²=1
2y²+y-1=0

Δ= b² - 4ac
Δ= (1)² - 4.2.-1
Δ= 1+8
Δ=9

y= -b +/- √Δ
         2a
y= -1 +/- √9
       2.2
y= -1 +/- 3
         4
Iy= -1 - 3 --> -4 --> -1
        4          4
IIy= -1+3 --> 2 -->  2
         4        4

Para y= -1
x= 1+2.-1
x=1-2
x=-1
(-1)

Para y=2
x=1+2.2
x=1+4
x=5
(5,2)

S={(-1)(5,2)}
1 5 1
A melhor resposta!
2014-08-04T00:11:24-03:00
X.y=1
x-2y=1 ---> x=1+2y

Substituindo:
(1+2y).y=1  
2y²+y-1=0
Δ=1² - 4.2.(-1)      y= (-1(+ou-)√9) / (2.2)= (-1(+ou-)3) / 4=
Δ=1+8                 y'= -2:4 = -1/2
Δ=9                     y''= -4/4 = -1
*Para y= -1/2, temos: (Não satisfaz)
x= 1+(2. -1/2)
x=1-1= 0  ∉
*Para y= -1, temos: (Satisfaz o sistema)
x= 1+(2. -1)= 1+(-2)= -1

2 3 2